Common Beliefs and the Existence of Speculative Trade - Zvika Neeman (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1993)
This paper shows that if rationality is not common knowledge, the no-trade theorem of Milgrom and Stokey (1982) fails to hold. We adopt Monderer and Samet's (1990) notion of common p-belief and show that when traders entertain doubts about the rationality of other traders, and even if these doubts are very small, arbitrarily large volumes of trade as well as rationality may be common p-belief for a large p. Furthermore, rationality and trade may simultaneously be known to arbitrary large (but finite) degree. The underlying intuition of the model is that, in trade situation, every trader may be rational but may believe tht the others are not fully rational. Thus, rational traders trade with each other, believeing that the other trader might be wrong, while they are right.
Keywords: 330